Efficient market hypothesis and shari'ah compliances stock return behaviour in Indonesia and Malaysia markets - Helma, Malini (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The development of Shari’ah compliances in Indonesia and Malaysia Markets is a proved that Shari’ah compliance is integral parts of the Islamic financial industry. The diversification of Islamic capital market product showed that both countries has become the pioneers and benchmark for Shari’ah product development in the world and Shari’ah compliance is one of the Islamic capital market product that has the biggest funding accumulation since the beginning of the introduction. The statistical process from linearity and volatility modeling, stock return predictability and Shari’ah compliance integration by using GARCH model specification showed that in term of return behaviour particularly volatility of Shari’ah compliances in Indonesia and Malaysia are vulnerable towards events and news that happened in both countries. Indonesia Shari’ah compliance is vulnerable to political news events that happened in Indonesia. Kuala Lumpur Shari’ah compliance is vulnerable to the social and economic news and events that happened in Malaysia. The result from calendar effect showed that investor in Shari’ah compliance in Indonesia and Kuala Lumpur Shari’ah compliance could earn abnormal return particularly in the month of December, February and October in Indonesia Shari’ah compliance. While, Kuala Lumpur Shari’ah compliance, January, October and April are the month where investor could earn abnormal return. Holiday effect prove to be exist in both Shari’ah compliance with the tendency to occur only on pre-holiday where most of investor showed happiness in welcoming holiday through their investing decision and behaviour. The result from Shari’ah compliances integration between Indonesia and Malaysia with selected Shari’ah compliances in the world showed that Indonesia and Malaysia has a strong correlation to each other, not only because of geographical closeness but also dependencies in term of social and economics. This research suggest that both Indonesia and Malaysia Shari’ah compliances should develop the trading mechanism, improving Shari’ah regulation and introduce Shari’ah compliances portfolio into a more wider investor, since both market are in semi strong form, both Indonesia and Kuala Lumpur Shari’ah compliances should focusing on creating a better platform for investor to provides efficient market and stability in stock return by improving the regulation and incentive distortion.